DETERMINATION OF THE BASIC PARAMETERS OF A HYDRAULIC JET PUMP SUPPLYING HYDRAULIC MIXTURES - Urishev, Bobaraim; Zhuraev, Sanzhar (Innovatsion texnologiyalar, 2024)
The article discusses issues related to finding a solution to the problem of siltation of the bottom of the water intake structure (front chamber and water intake chambers) of pumping stations. A new device has been proposed, based on the use of a hydraulic jet pump, which makes it possible to clean the fore-chambers from deposited sediment at its bottom without stopping the pumping station, i.e. during the operation of the units. New analytical equations have been obtained that reflect the pressure-flow characteristics of a hydraulic jet pump for pumping clean water and hydraulic mixtures. By comparing the graphs of pressure-flow characteristics, it was established that the results of calculating the pressure-flow characteristics of a hydraulic jet pump using the obtained analytical expression correspond to the results obtained by other researchers. The values of the pressure-flow characteristics of the process of removing hydraulic fluid from the fore-chamber of a pumping station using a hydraulic jet pump are determined.